Real-time RT-PCR internal quality control optimization for qualitative detection of SARS-CoV-2 - Torres-Gamarra, Giancarlo (2023)
Objective: To optimize the internal quality control of real-time RT-PCR for the qualitative detection of SARS-CoV-2, using the Cq values ​​of negative and positive controls. Material and method: Prospective-longitudinal study. The sample consisted of 143 Cq values ​​for the negative aliquot and extraction controls, as well as for the positive control. The normal distribution of Cq values ​​was analyzed using the Anderson-Darling (AD) test and randomness tests were applied. Control limits were calculated from 51 Cq values, and then, using control charts, to monitor 92 Cq values ​​obtained from November 2020 to March 2021. Lot acceptance and Cpk indices were evaluated as optimization indicators. The calculations were made with the Minitab program. Results: The batches of Cq values ​​were accepted and Cpk indices higher than 1.33 were obtained for the three types of control. Discussion: There are no published studies that apply statistical quality control to the qualitative detection of SARS-CoV-2. Conclusions: It is possible to use the Cq values ​​of the controls to optimize the internal quality control of real-time RT-PCR for qualitative detection of SARS-CoV-2, as if it were a quantitative technique.